The state of physician office-based health information technology in Connecticut: current use, barriers and future plans. - Mattocks, Kristin; Lalime, Kenneth; Tate, Janet P; Giannotti, Tierney E; Carr, Kevin; Carrabba, Angelo; Blum, Thomas; Meehan, Thomas P (Connecticut medicine, 2007)
Qualidigm and the Connecticut State Medical Society-Independent Practice Association (CSMS-IPA), Inc. have conducted a survey of the physicians participating in the CSMS-IPA to assess current use of health information technology in their offices and their plans for future use. The survey was conducted to assist eHealth Connecticut, a Connecticut-based nonprofit organization, in its charge to promote electronic health information exchange in Connecticut. The survey was distributed to 2,366 medical offices representing 6,956 physicians in Connecticut. Survey results revealed that the most commonly utilized types of technology were practice management systems (70%) and e-mail (64%). The most common barriers to the adoption of new technologies were cost (71%) and time requirements (39%). Primary-care providers and small practices were more likely to cite cost as a barrier to technology implementation. Despite these challenges, many physicians reported plans to implement electronic medical records (25%) or electronic prescribing (20%) in the next year.
Keywords: Biomedical Technology; Connecticut; Forecasting; Humans; Information Management; Internet; Medical Records Systems, Computerized; Physicians' Offices; Practice Management, Medical